Evaluation of antibacterial activity of propolis on regenerative potential of necrotic immature permanent teeth in dogs - M. M. El-Tayeb; A. M. Abu-Seida; S. H. El Ashry; S. A. El-Hady (BMC, 2019)
Abstract Background This study evaluated the antibacterial efficiency and ability of propolis to promote regeneration of immature permanent non-vital dogs' teeth. Methods Ninety six immature permanent premolars teeth in 6 mongrel dogs were divided randomly into: experimental teeth (N = 72) and control teeth (N = 24). Periapical pathosis was induced in all experimental and positive control teeth. Experimental teeth were classified according to the used intra-canal medication into: group I (N = 36), propolis paste was used and group II (N = 36), triple antibiotic paste (TAP) was used. Bacteriologic samplings were collected before and after exposure to intra-canal medicaments. After the disinfection period (3 weeks), revascularization was induced in all experimental teeth. Each group was subdivided according to the root canal orifice plug into: subgroup A (N = 18), propolis paste was used and subgroup B (N = 18), mineral trioxide aggregates (MTA) was used. Each subgroup was further subdivided according to the evaluation period into 3 subdivisions (6 teeth each): subdivision 1; after 2 weeks, subdivision 2; after one month and subdivision 3; after 2 months. Positive control group had 12 teeth with induced untreated periapical pathosis. Negative control group had 12 untouched sound teeth. All teeth were evaluated with radiography and histology. The bacteriologic and radiographic data were analyzed using repeated measures ANOVA and post-hoc Tukey tests. The histologic data were analyzed using Kruskal-Wallis test, Mann-Whitney U test with Bonferroni's adjustment and Chi-square test. The significance level was set at P ≤ .05. Results There was no significant difference in the antibacterial effectiveness between TAP and propolis groups (P > .05). In all subdivisions, there was no significant difference between the experimental groups in terms of increase in root length and dentin thickness, decrease in apical closure, new hard tissue formation, vital tissue formation inside the pulp canal and apical closure scores (P > .05). Conclusion Propolis can be comparable with TAP as a disinfection treatment option in regenerative endodontic. As a root canal orifice plug after revascularization of necrotic immature permanent teeth in dogs, propolis induces a progressive increase in root length and dentin thickness and a decrease in apical diameter similar to those of MTA.